2018
DOI: 10.1016/j.crvi.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of estrogen receptors, P450 aromatase, PCNA and p53 in high-fat-induced impairment of spermatogenesis in rats

Abstract: Obesity and overweight are frequently associated with male subfertility. To address new findings on the players involved in the obesity-induced impairment of spermatogenesis, we used a high-fat diet-induced overweight-rat model. Following four weeks of high-fat diet, the organization of seminiferous epithelium was affected, and tubules lumen showed immature/degenerated cells, typical signs of hormonal imbalance and testicular damage. Real-time PCR analysis allowed us to detect increased levels of ERα and decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…In particular, we demonstrated that the germ cells, as well as somatic cells, are positive to antibodies for enzymes involved in the sex hormones production, that is, StAR, 3β-HSD, 17β-HSD, P450 arom, 5α-Red Rosati, Agnese, Abbagnale, et al, 2019). Here in, we have for with what has already been highlighted in other animal models, as bivalvia mollusk , amphibians , reptiles , and mammals (Bilińska, Schmalz-Frączek, Kotula, & Carreau, 2001;Carreau et al, 2011). In particular, in Coturnix testis, as well as showed in Podarcis testis , the steroidogenic process could be quite relevant during the spermiogenesis, that is, in spermatids and testicular spermatozoa.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…In particular, we demonstrated that the germ cells, as well as somatic cells, are positive to antibodies for enzymes involved in the sex hormones production, that is, StAR, 3β-HSD, 17β-HSD, P450 arom, 5α-Red Rosati, Agnese, Abbagnale, et al, 2019). Here in, we have for with what has already been highlighted in other animal models, as bivalvia mollusk , amphibians , reptiles , and mammals (Bilińska, Schmalz-Frączek, Kotula, & Carreau, 2001;Carreau et al, 2011). In particular, in Coturnix testis, as well as showed in Podarcis testis , the steroidogenic process could be quite relevant during the spermiogenesis, that is, in spermatids and testicular spermatozoa.…”
Section: Discussionmentioning
confidence: 71%
“…In the testis, they are primarily produced in Leydig and Sertoli cells, where they are synthesized from a common precursor, the cholesterol, via a series of enzyme-catalyzed reactions (Miller, 1988). However, in recent years it has been showed that germ cells also produce sex hormones Carreau et al, 2011;Prisco et al, 2017;Rosati, Agnese, Abbagnale, et al, 2019;Rosati, Santillo, et al, 2017). Indeed, more recently, in some seasonal breeding, as the bivalve mollusk…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations